2007
DOI: 10.1002/app.26152
|View full text |Cite
|
Sign up to set email alerts
|

Dispersing mechanism of carboxymethyl starch as water‐reducing agent

Abstract: In this article, by using zeta (z) potential analyzer, X-ray photo spectroscopy, and UV-visible adsorption spectrophotometer, the adsorption characteristics and surface electrochemical properties of carboxymethyl starch (CMS) as water-reducing agent on cement particles and its effects on the fluidity of cement paste were studied in comparison with traditional naphthalene sulfonic acid-formaldehyde condensates, whose dispersion ability mainly depends on electrostatic repulsive force caused by z-potential. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Beside the physicochemical properties evaluating techniques mentioned above there are more testing methods, such as: biodegradability 52, in vivo digestibility 56, light transmittance of CMS paste or solution 28, ζ‐potential and absorption capacity 52, 57, 58, conductivity of CMS dispersions 59. They are not the subject of this paper as are strictly related to specific CMS application.…”
Section: Methods Of Structure and Physicochemical Properties Of Cms Dmentioning
confidence: 99%
“…Beside the physicochemical properties evaluating techniques mentioned above there are more testing methods, such as: biodegradability 52, in vivo digestibility 56, light transmittance of CMS paste or solution 28, ζ‐potential and absorption capacity 52, 57, 58, conductivity of CMS dispersions 59. They are not the subject of this paper as are strictly related to specific CMS application.…”
Section: Methods Of Structure and Physicochemical Properties Of Cms Dmentioning
confidence: 99%
“…This is due to the presence of comb‐like side‐chain structures with functional groups in the molecule, which are adsorbed and act as barriers keeping the cements particles far apart from each other to ensure proper hydration and dispersion 33–35 . On the other hand, natural carbohydrate water reducers like cellulose, starch or their derivatives can disperse cement particles via the electrosteric effect because of their high molecular weights from repeating glucose units and the presence of charged ‐OH and carboxyl functional groups within their structures 36 . Studies have thus shown that the mechanism of dispersion of these bio‐based water reducers have potential impact on the final properties of concrete such as the setting time 37 .…”
Section: Introductionmentioning
confidence: 99%
“…ese researches show that, for all the polysaccharides such as starch, cellulose, and so on, through rational molecular design and the appropriate reaction conditions, they are probably prepared into water-reducing agents with high efficiency in concrete [15][16][17][18]. However, the systematic preparation process of the cellulose-based water-reducing agent is rarely reported.…”
Section: Introductionmentioning
confidence: 99%